Strengthening the delivery of asthma and chronic obstructive pulmonary disease care at primary health-care facilities: study design of a cluster randomized controlled trial in Pakistan - Muhammad Amir Khan; Maqsood Ahmed; Shirin Anil; John Walley (Taylor & Francis Group, 2015)
Background: Respiratory diseases, namely asthma and chronic obstructive pulmonary disease (COPD), account for one-fourth of the patients at the primary health-care (PHC) facilities in Pakistan. Standard care practices to manage these diseases are necessary to reduce the morbidity and mortality rate associated with non-communicable diseases in developing countries. Objective: To develop and measure the effectiveness of operational guidelines and implementation materials, with sound scientific evidence, for expanding lung health care, especially asthma and COPD through PHC facilities already strengthened for tuberculosis (TB) care in Pakistan. Design: A cluster randomized controlled trial with two arms (intervention and control), with qualitative and costing study components, is being conducted in 34 clusters; 17 clusters per arm (428 asthma and 306 COPD patients), in three districts in Pakistan from October 2014 to December 2016. The intervention consists of enhanced case management of asthma and COPD patients through strengthening of PHC facilities. The main outcomes to be measured are asthma and COPD control among the registered cases at 6 months. Cluster- and individual-level analyses will be done according to intention to treat. Residual confounding will be addressed by multivariable logistic and linear regression models for asthma and COPD control, respectively. The trial is registered with ISRCTN registry (ISRCTN 17409338). Conclusions: Currently, only about 20% of the estimated prevalent asthma and COPD cases are being identified and reported through the respective PHC network. Lung health care and prevention has not been effectively integrated into the core PHC package, although a very well-functioning TB program exists at the PHC level. Inclusion of these diseases in the already existent TB program is expected to increase detection rates and care for asthma and COPD.